Democracy in the Workplace and at Home Finding Freedom, Liberty and Justice in the Lived Environment - Booze, Randall Ray (Cambridge Scholars Publishing, 2014)
This book takes a unique look at democracy and how foundational concepts of democracy like freedom, liberty and justice play an important role in everyday lives and work and home environments. More importantly, the book looks at how lived environments that lack these concepts can negatively impact health and well-being. The book identifies opportunities for improvement in work and home environments through the introduction of the foundational concepts of democracy and how these concepts can improve humans' everyday lives through various laws that have been established to protect democratic rights within these lived environments. The book also provides an analysis of research participants' views related to having various democracy conditions within work and home environments, and demonstrates how various technologies can be used to improve humans' ability to create more democratic, healthy, and productive work and home environments